Applying optimization techniques on cold-formed C-channel section under bending - El-Lafy, Heba F.; Elgendi, Elbadr O.; Morsy, Alaa M. (Zielona Góra: Uniwersytet Zielonogórski)
There are no standard dimensions or shapes for cold-formed sections (CFS), making it difficult for a designer to choose the optimal section dimensions in order to obtain the most cost-effective section. A great number of researchers have utilized various optimization strategies in order to obtain the optimal section dimensions.
Keywords: cold-formed sections; single optimization; multi-objective optimization; genetic algorithms; effective width method; C-channel beams